Isolation of Mesenchymal Stem Cells (MSCs) from Wharton’s Jelly (WJ) Tissue of Human Umbilical Cord (hUC); a Protocol - Ahangari, Fatemeh; Mirsanei, Zahra; Soudi, Sara; Ghaffari Khaligh, Sahar; Soufi, Sara; Hashemi, Seyed Mahmoud (Student Research in Translational Medicine, 2023)
Mesenchymal stem cells (MSCs) with their spindle like shapes are a lineage of stem cells with the capacity to self-renew and differentiate into osteoblasts, adipocytes, and chondrocytes and with CD105, CD73, and CD90 expression and the lack of CD34, CD14, CD45, and HLA - DR expression. The immunomodulatory, angiogenic, antiapoptotic, antimicrobial, and antioxidative characteristics of these cells made them more attractive in the field of cell - therapy for several autoimmune and inflammatory diseases, including diabetes, neurological disorders, sepsis, cardiac ischemia, and GvHD. For this reason, various protocols have been proposed to isolate mesenchymal stem cells from different tissue sources, such as adipose tissue (AT), umbilical cord (UC), Wharton’s jelly (WJ), bone marrow (BM), dental pulp, and even menstrual fluid. Considering the ease of access to the umbilical cord tissue and the fact that this tissue is rich in MSCs with embryonic origin and higher proliferation rate and lower senescence of the cells, the umbilical cord became a suitable source for explant MSC culture. In this study, we decided to introduce an explant culture protocol of MSCs that is less expensive and cost - effective achieving a high yield of MSCs.